Automated driving behaviour impacts in mixed road traffic environment - Macedo, Eloísa (2021)
The increasing levels of automated functions in vehicles are expected to reshape the future of road transport. Soon, connected, automated and conventional vehicles will share the roads, and it is essential to understand the impacts of such new road environment under several components such as traffic performance, climate change, air quality. This paper is devoted to presenting a study focusing on a multi-criteria traffic assignment model based on minimizing travel time, distance travelled and pollutant emissions considering various automated vehicles (AVs) with different driving behaviours scenarios in a road network of conventional vehicles (CVs). For that purpose, a case study of an intercity corridor was used considering current traffic demand. Results show AVs introduction can in fact significantly contribute to reducing emissions provided their behaviour is a combination in its majority of cautious AV. Results suggest replacing 20% of AV aggressive fleet by cautious yields worst results regarding emissions, even when compared to 100% aggressive AVs. The proposed approach is relevant for decision making, particularly for strategic policymaking and planning, and can help authorities achieve their sustainable mobility goals, especially to anticipate the impacts of AVs introduction in the near future.